Implementing the Three-Way Marketing Public Relations Strategy in Indonesia's Railway Sector: A Qualitative Study on PT KAI Operational Area 7 Madiun - Farani, Dinesh Basti; Ayutika, Riza Dessy Nila; Arifin, Ressa Nidya (Majapahit Journal of Islamic Finance and Management, 2025)
The increasing types and models of transportation in Indonesia encourage companies to strengthen marketing strategies so that their companies can exist for a long time. Business competition requires companies to intensively carry out promotional activities by combining public relations in marketing activities. Marketing Public Relations is considered capable of expanding market share and becoming a company communication tool to achieve business goals. The purpose of this research is to determine the Marketing Public Relations strategy at the PT KAI (Persero) Daop 7 Madiun Passenger Transport Unit. The method used in this research is descriptive qualitative. Meanwhile, data for this research will be taken by conducting interviews, observation and documentation. The results of research in the field can be concluded that the implementation of Marketing Public Relations strategies in Passenger Transport Units is through a Three Ways Strategy including Pull Strategy, carried out by uploading promotional content on social media, advertising on print media and holding events on certain holidays. Push Strategy, carried out by providing discounts to customers and carrying out BPTV (Boarding Pass Through Value) cooperation programs with several merchants. Pass Strategy, carried out by improving services and carrying out social responsibility (CSR) activities .